Decision by Opinion Score Method (DOSM) a novel solution for multi criteria decision making problem - Al Haideri, Abdulhadi Qays Abdulhadi (Tanjong Malim, 2020)
Decision by Opinion Score Method (DOSM) a novel solution for multi criteria decision making problem by Al Haideri, Abdulhadi Qays Abdulhadi